Final report - Meeting on The Link Between Technical and Non-formal Education (CINTERPLAN, 1981)
After briefly describing the work already accomplished in the field of technical and nonformal education and its objectives, the document presents the statements made during the meeting and the work of the countries that took part in it, namely, Barbados, Dominica, Grenada, Guyana, St. Lucia, and St. Vincent and the Grenadines
Keywords: Technical education